(untitled) (Research, Society and Development, 2020)
The use of water with high electrical conductivity in irrigation has been recurrent in the rain-dependent areas in the Bahian semiarid, which can lead to the degradation of the chemical and physical characteristics of the soils. The objective of this work was to evaluate the chemical characteristics of a Inceptisol under irrigation with brackish water, cultivated with forage palm in the district of Juremal Juazeiro BA. Soil samples were collected with and without palm cultivation in different periods, before and after the rainy season (2018/2019) at two depths (0-0.20m and 0.20 -0.40m). Exchangeable bases, electrical conductivity and pH were determined. There were no risks regarding salinization and sodification in the area under cultivation for the longest time, however the presence of the saline character was observed in the area under cultivation for the shortest time. There was a reduction in the sum of bases and electrical conductivity in the samples collected after the rainy season.